Increased thermal stability of activated N2 adsorbed on K-promoted Ni{110}. Issue 32 (8th August 2017) - Liu, Tao; Temprano, Israel; Jenkins, Stephen J.
Abstract : The role of potassium in promoting the adsorption, and modulating the polarisation, of dinitrogen is investigated by RAIRS and DFT. Abstract : Industrial synthesis of ammonia takes place at high temperatures and pressures via the dissociative adsorption of molecular nitrogen on a transition metal catalyst. In contrast, biological ammonia synthesis occurs under ambient conditions via the hydrogenation of intact molecular nitrogen at the active site of an enzyme. We hypothesise that the latter process may be mimicked within an inorganic system if the intact nitrogen molecule can be polarised, rendering it particularly susceptible to attack by hydrogen. Furthermore, by analogy with the surface chemistry of carbon monoxide at alkali-modified nickel and cobalt surfaces, we consider whether such a polarisation may be achieved by coadsorption with potassium on the same or similar transition metals. Here, we report on reflection absorption infrared spectroscopy results, interpreted with the aid of first-principles density functional calculations, which reveal both similarities and differences between the behaviour of carbon monoxide and nitrogen. Importantly, our calculations suggest that the surface-induced dipole of molecular nitrogen can indeed be enhanced by the coadsorbed alkali metal.